Combination of flood hazard, exposure and vulnerability in determining flood risk in Kelantan, Malaysia - Arham Muchtar Achmad Bahar (2022)
Floods have been reported to be the main disasters in many countries across the globe. Malaysia, which is mostly influenced by seasonal monsoon floods has a long history of floods in past, which have heavily impacted on the people affecting livelihood, financial loses, infrastructure damage including roads, railway, bridges, vehicles, properties etc. One among them is extreme flood of December 2014, which created a great havoc on Kelantan state of Malaysia and paralyzed all aspects of life. The present thesis is focused on this flood event with an aim to segregate areas of risks during extreme flooding in order to manage vulnerable areas preferably through assessment of flood hazard, flood exposure and flood vulnerability. The methodology deployed involves a combination of desktop studies using secondary flood government data, flood reports, published papers, interviews and questionnaires. The study confined to rural areas including Manik Urai and Kuala Pergau and urban areas represented by Kuala krai and Gua Musang deploys GIS and statistical data processing applications. As per the results from flood hazard index, flood exposure index and flood vulnerability index, the entire study area can be categorized into three risk zones namely low, moderate and high. The areas of high risk zone include Kuala Krai, Manik Urai and Kuala Pergau. Moreover, flood risk is comparatively higher in rural area like Manik Urai and Kuala Pergau especially in terms of vulnerability. As far as Physical vulnerability is concern, Bandar Kuala Krai is most vulnerable followed by Manik Urai, Kuala pergau and Gua Musang. The present study provides indexing of elements at risk which will help decision makers to prioritize the aspects of flood management in Kelantan. The awareness about appropriate response to floods among flood victims need to be eradicated through empowerment and engagement, which will enhance their ability to respond to floods timely and effectively.